GST implications of ecommerce and goods warehousing - Pearce, Prafula; Pinto, Dale (2019)
Australian consumers are increasingly purchasing goods from other countries, especially through online platforms such as eBay. Online platforms and logistics companies are increasingly providing overseas sellers with a local address, a warehouse and a local bank account to facilitate faster delivery of products to online shoppers. By using a hypothetical scenario, this article explores the GST implications when foreign online sellers use integrated warehouse-focused supply chain solutions under the “ship first, sell later” model. The article questions whether the underlying reason for the enactment of the Treasury Laws Amendment (GST Low Value Goods) Act 2017 (Cth) that small Australian businesses are not unfairly disadvantaged by low-value imported goods has been fully achieved. The proposed solution could be the introduction of a “foreign business number” that permits foreign entity identification for the purposes of not only GST and income tax, but also the Customs Act 1901 (Cth) and Australian consumer law.